Depression as a predominant factor for activities of daily living among elderly - Giovanny, Audrey Carissa; Handajani, Yvonne Suzy; Turana, Yuda; Kristian, Kevin (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to provide an overview of the ability to perform activities of daily living (ADL) in the elderly population and to identify associated factors. Methods: A cross-sectional study was conducted with 100 community-dwelling participants aged 60 and older in West Jakarta. Sociodemographic data, the Barthel Index, the Berg Balance Scale, the Fried Frailty Index, and the Geriatric Depression Scale were collected by interview. Chi-Square and multiple logistic regression analyses were used for the bivariate and multivariate analyses. Results: The majority of participants were women (71%), aged 60-74 years (75%), with education levels of 12 years or more (90%). Fifteen percent of elderly participants experienced problems with ADL. Chi-square analysis showed significant associations between ADL impairment with age (p=0.006; OR=4.57; 95%CI: 1.454-14.368), balance (p=0.023; OR=10.38; 95%CI: 1.567-68.595), and depression (p=0.006; OR=5.00; 95%CI: 1.468-17.033). Multiple logistic regression analysis identified depression as the most dominant risk factor affecting ADL, increasing the risk by 4.02 times. Conclusion: This study highlights age, body balance, and depression as potential contributors to ADL impairment, with depression emerging as the predominant risk factor. Both physical and mental health should be considered essential for preserving ADL function in the elderly.